Some properties of fuzzy cone symmetric spaces - Tarkan Oner (Journal of Hyperstructures, 2023)
In this work, we give a fuzzy analogy of cone symmetric spaces that we call fuzzy cone symmetric spaces. Since these structurere obtained by omitting the triangle inequality in fuzzy cone metric spaces, there are topological degenerations. After mentioning these degenerations, we investigate the relationship between cone (sym)metric and fuzzy cone (sym)metric spaces.